The spectrophotometric determination of visual spectral sensitivity of sutchi catfish Pangasianodon hypophthalmus - Nai, Han Tan; Mukai, Yukinori; Okawa, Ryo; Anraku, Kazuhiko (2018)
Visual spectral sensitivity refers to the relative sensitivity of the eye towards different wavelengths of light. In fish, their eyes show specific adaptation in sensitivity to match the different light environments in their natural habitats. Sutchi catfish Pangasianodon hypophthalmus is one of the commercially cultured freshwater fish species in Southeast Asia. The present study aimed to understand the visual spectral sensitivity of sutchi catfish through spectrophotometric analyses of the spectral absorbance of retinal wholemounts for the goal to establish appropriate lighting conditions in aquaculture system to improve growth performance of sutchi catfish. In the dark room, the retinae of sutchi catfish were isolated under a dissecting microscope with the help of a night vision goggles. The isolated retinae were cut into approximately 9 mm2 -size pieces. Each retina sample was then placed on a coverslip with a drop of saline solution and covered with another coverslip. Spectral absorbance of retinal wholemounts was measured by means of a portable modular spectrophotometer. A broad wavelength LED was used as the main light source, while blue (peak at 454 nm), green (520 nm), yellow (590 nm) and red (632 nm) LEDs were used as the supplementary light sources for flashing. Spectrophotometric measurement data were used to generate spectral absorbance curves. Comparison between the peaks of the curves showed that red light exposure induced a prominent shift of peak spectral absorbance towards shorter light wavelengths, suggesting the eyes of sutchi catfish had spectral sensitivity for light wavelength of red.